SINTESIS FOTOKATALIS TiO2-S DAN KINETIKA DEGRADASI METILEN BIRU - , SOFYURRIZAL ADI TAMA, Dr. Eko Sri Kunarti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
TiO2-S has been successfully synthesized The aim of this research is to study the effect of sulphur addition to the photocatalytic properties of TiO2 and the study of its photodegradation kinetics against methylene blue. Modification of TiO2 was conducted as follows